Firefly the game [games] : find a crew, find a job, keep flying. (Gale Force Nine, 2013)
Find a crew: Travel to different locations, handpicking the best crew and gear. Purchase upgrades to customize your Firefly, readying yourself for the challenges ahead. Find a job: Deal with contacts, reputable or not, to secure desperately needed work and build your reputation as a successful captain. Avoid morally questionable jobs or grab whatever work is offered. You do the job, you get paid. Keep flying: Dodge bloodthirsty Reavers and evade Alliance patrols as you navigate the 'Verse, fighting to keep your crew safe and your ship shiny. Rival captains may be looking to hire away your crew or tip off the Alliance to your plans. Welcome to the 'Verse.